Can Water Undermine Growth? Evidence from Ethiopia - Sadoff, Claudia (World Bank, Washington, DC, 2012)
In Ethiopia the centrality of water is clear. With little water resources infrastructure, relatively weak management institutions and capacity, extreme hydrological variability and seasonality, and a highly vulnerable economy, Ethiopia faces an enormous challenge in building the minimum platform of water infrastructure and management capacity needed to achieve water security. But until water security is achieved, growth will continue to be severely constrained. A World Bank study (World Bank 2006) estimated the magnitude of the impacts of high water variability on growth and poverty so that the government can better manage water and manage other parts of the economy (trade, transport) to reduce the impacts of water shocks. The study found that considering the effects of water variability reduced projected rates of economic growth by 38% per year and increased projected poverty rates by 25% over a twelve year period. Furthermore, the variability of rainfall increased value-added of water investments, such as irrigation, that reduce vulnerability to rainfall. The study also found that transport infrastructure played a major role in the inability of local economies to adjust to localized crop failures, as it allows areas with food surpluses to sell to areas in food deficit. This analysis, undertaken in cooperation with the Ethiopian government, helped to make the issue of water resource management a central focus of the government's national poverty reduction strategy.